Pengembangan Media Pembelajaran Simple Submarine Berbasis Teknologi Sederhana untuk Meningkatkan Literasi Sains Peserta Didik - Yulia Hasan; Gunawan Gunawan (Indonesian Journal of STEM Education, 2023)
The ability of science literacy in students in Indonesia is still relatively lacking or low, which is characterized by the inability of students to use scientific knowledge, identify relevant questions, and draw conclusions based on scientific facts. This research method uses Research and Development (R&D). Some of the factors that trigger students' low science literacy are school infrastructure, learning facilities and facilities, resources in schools, and management implemented by schools. Based on the results of observations and interviews at Nurul Mujahiddin NW Penimbung Islamic Junior High School, the technology media facilities are inadequate, as a result of which the understanding of science literacy is low.  This can also be assessed through the lack of activity of students and when given questions they are unable to answer the questions asked.  The low science literacy ability with minimal facilities is what is the innovation in the creation of this learning media by utilizing items that are easy to find and get in the environment around the school. So the author is interested in raising the title "Development of Simple Submarine Learning Media Based on Simple Technology for Science Literacy of Students". With the aim that the author can help various schools that have limited technology media facilities by utilizing simple submarines as simple technology-based learning media so that they can improve science literacy in students.